2013
DOI: 10.1002/hlca.201300118
|View full text |Cite
|
Sign up to set email alerts
|

Diterpenoids from the Wood of Cunninghamia konishii

Abstract: Investigation of the wood of Cunninghamia konishii resulted in the isolation and characterization of one new abietane diterpenoid, (6α,7β)‐7,8‐epoxy‐6‐hydroxyabieta‐9(11),13‐dien‐12‐one (1), and two new labdane diterpenoids, (12R)‐12‐hydroxylabda‐8(17),13(16),14‐trien‐19‐oic acid (2) and (12R)‐12‐hydroxylabda‐8(17),13(16),14‐trien‐18‐oic acid (3). The structures of these new compounds were elucidated by analysis of their spectroscopic data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Three new sesquiterpenoids, 2α-hydroxy-3,3,6α,9β-tetramethyltricyclo[4,3,2 1,4 ]undecane (1), 11-acetoxyeudesman-4β-ol (4), and 2α,3β-dihydroxy-4β-methyl-6,8,10-cadinatriene (6), four known sesquiterpenoids (2, 3, 5, and 7), together with eight known diterpenoids (8)(9)(10)(11)(12)(13)(14)(15), were isolated from the wood of C. konishii. Among them, four sesquiterpenoids (1, 4, 5, and 6) and eight diterpenoids (8)(9)(10)(11)(12)(13)(14)(15), five of which we reported previously (11)(12)(13)(14)(15), were evaluated for their anti-inflammatory activity and the results showed that compounds 10 and 15 exhibited moderate inhibitory effects on lipopolysaccharides (LPS)-induced nitric oxide production in RAW264.7 cells.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Three new sesquiterpenoids, 2α-hydroxy-3,3,6α,9β-tetramethyltricyclo[4,3,2 1,4 ]undecane (1), 11-acetoxyeudesman-4β-ol (4), and 2α,3β-dihydroxy-4β-methyl-6,8,10-cadinatriene (6), four known sesquiterpenoids (2, 3, 5, and 7), together with eight known diterpenoids (8)(9)(10)(11)(12)(13)(14)(15), were isolated from the wood of C. konishii. Among them, four sesquiterpenoids (1, 4, 5, and 6) and eight diterpenoids (8)(9)(10)(11)(12)(13)(14)(15), five of which we reported previously (11)(12)(13)(14)(15), were evaluated for their anti-inflammatory activity and the results showed that compounds 10 and 15 exhibited moderate inhibitory effects on lipopolysaccharides (LPS)-induced nitric oxide production in RAW264.7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…LPS can significantly increase the level of nitric oxide (NO) in macrophages through activation of iNOS [29]. In this study, the inhibitory activity toward NO production of four sesquiterpenoids (1, 4, 5, and 6) and eight diterpenoids (8)(9)(10)(11)(12)(13)(14)(15) was evaluated by measurement of nitrite/nitrate in LPS-stimulated RAW 264.7 cells. To search for the appropriate concentrations for the above assay, these 12 compounds were first tested their cytotoxic activity against the RAW 264.7 cells, and no significant cytotoxic activities were observed under all tested concentrations (Table 3).…”
Section: Inhibitory Activity Against Nitric Oxide Productionmentioning
confidence: 99%
See 3 more Smart Citations